A proposed model representing the relationships between user characteristics, computer exposure and musculoskeletal symptoms in children. - Soares, Marcelo M.; Jacobs, Karen; Harris, C.; Straker, L.; Smith, A.; Pollock, C. (Work)
Children's computer exposure is rapidly growing. Several studies have suggested children using computers may be at risk of developing musculoskeletal symptoms. General models and theories relating to the causality of negative musculoskeletal outcomes in adult workers demonstrated relationships between workplace factors and musculoskeletal outcomes. When examining children's computer exposure it is evident that their use is different. Even though risk factors may be similar, due to the nature of children and their computer environments, the potential risk factors and thus a proposed model of causal relationships between exposure and outcomes may differ. Objective: To develop a model of factors influencing computer exposure and musculoskeletal symptoms in children. Methods: 1351 children (or their parents for Year 1 children) in school Years 1, 6, 9 and 11 (ages ~ 6,11,14,16 years) from 10 schools in Western Australia were surveyed on a range of user characteristics, computer exposure and musculoskeletal symptoms. Results: Potential risk factors for childrens' computer exposure and musculoskeletal outcomes were multivariable. Factors such as age, gender, somatic complaints, flow, computer anxiety, computer, TV and physical activity exposure, and SES were related to computer exposure and children's reports of musculoskeletal symptoms. Significance: Developing a child-related computer exposure model to understand relationships between potential risk factors and musculoskeletal symptoms will assist academics, teachers and parents to develop a better understanding of the risk factors for children's computer exposure.